2017
DOI: 10.1002/jctb.5488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sludge age on microbial consortia developed in MFCs

Abstract: BACKGROUND This work is focused on the assessment of the performance of mini‐scale air‐breathing microbial fuel cells (MFCs), by monitoring the evolution of the bio‐electrogenic activity for a period of 40 days and by comparing the microorganisms populations developed in each of the MFCs after this period. RESULTS Five MFCs were operated at sludge ages ranging from 1.4 to 10.0 days. Results showed the superb performance of the MFC operating under a sludge age of 2.5 days. Desulfuromonas, Syntrophothermus, Soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…As observed in Figures a and b, any modification in SA reduces the CCV when compared with the CCV reference value at a SA of 24 d which was the reference used in our previous study of the influence of HRT . The important influence of SA on the electrochemical performance has been reported in the literature and is based on the evidence that SA directly influences the composition of the microbial consortia in the anodic compartment . Based on this argument, the EGMs develop more favorably with the application of a SA of 24 d. In this case, a large amount of redox mediator (mediated electron transfer, MET) may be produced by the suspended EGM.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As observed in Figures a and b, any modification in SA reduces the CCV when compared with the CCV reference value at a SA of 24 d which was the reference used in our previous study of the influence of HRT . The important influence of SA on the electrochemical performance has been reported in the literature and is based on the evidence that SA directly influences the composition of the microbial consortia in the anodic compartment . Based on this argument, the EGMs develop more favorably with the application of a SA of 24 d. In this case, a large amount of redox mediator (mediated electron transfer, MET) may be produced by the suspended EGM.…”
Section: Resultsmentioning
confidence: 99%
“…This allows for a faster development rate and a higher value for VSS. The differences in the operational conditions (cell design, operation mode, substrate concentration, start‐up conditions, substrate type and the sequence chosen for the SA study) can explain the difference between our results and other results found in the literature . Another interesting feature can be derived from the fact that the maximum concentration of VSS (microorganisms) is achieved at shorter SAs compared to the maximum CCV.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations